Kur’ân’da geçen ( َ ل َ علَّ ) edatının anlamları ve meallere yansımaları - (:unkn) unknown (My University, 2012)
Arapçada bir edat olarak işlev gören ( َ ل َ علَّ ), Kur’ân-ı Kerîm’de 129 yerde değişik bağlamlarda kullanılmıştır. ( َ ل َ علَّ ) kelimesi buralarda, dilin imkân verdiği farklı anlamlara (tereccî, ta‘lîl ve teşvik vb.) gelmektedir. Söz konusu anlamlardan ilki olan tereccî/ummak, “her şeyi hakiki mahiyetiyle bilen Allah Teâlâ’ya nisbet edilemeyeceği” gerekçesiyle müfessirlerce, “tereccînin muhatap için geçerliliği” şeklinde yorumlanmıştır. Bu nüans, bazı Türkçe meallerde yansıtılırken çoğunda yansıtılmamıştır. Buna ilaveten َ ل َ علَّ) ) edatının (nehiy gibi) farklı manalarından bir kısmı kimi Türkçe meallerde yer alırken, kimilerinde, ya yer almamış ya da bağlama uygun tercüme edilmemiştir.

The word ( َ ل َ علَّ ) functions as a preposition in the Arabic language. It has been used one hundred and twenty-nine times in The Holly Qur’an. The word ( َ ل َ علَّ ) contains different meanings in the language according to the context, for example hope, cause, encourage etc. According to the commentators, ‘hope’ being the first of such meanings, is valid for interlocutor and not for God, because God knows everything at its true essence. While this nuance was reflected in some Qur’an translations, it was ignored in most. In addition, while some of the various meanings of the preposition ( َ ل َ علَّ ), for example prohibition, were mentioned in some Qur’an translations, it has not been placed in the others or the translations were not suitable for the context.
The meanings of the word "la'alla" ( َ ل َ علَّ ) in the Qur'an and their reflections into Turkish translations
Keywords: Din Bilimi